1996
DOI: 10.1111/j.1600-0668.1996.t01-1-00006.x
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Office Furniture, Workstation Layouts, Diffuser Types and Location on Indoor Air Quality and Thermal Comfort Conditions at Workstations

Abstract: Many factors affect the airflow patterns, contaminant removal efficiency and the indoor air quality at individual workstations in office buildings. The effects of office furniture design and workstation layouts on ventilation performance, contaminant removal efficiency and thermal comfort conditions at workstations were studied. The range of furniture configurations and environmental parameters investigated included: 1) partition heights, 2) partition gap size, 3) diffuser types, 4) supply air diffuser locatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 3 publications
(1 reference statement)
0
5
0
Order By: Relevance
“…Semi-open partitions between occupants can be used to form a personal cubical around each occupant to change the air distribution pattern and reduce the cross contamination (Shaw et al 1993a&b, Zhang et al 1994, Haghighat et al 1996, Kong, Zhang, and Wang 2014, and Kong 2019. Concentrations in a non-source containing cubical can be reduced by a factor of 1.1 to 3.6 in mixing type ventilation system with square or linear ceiling air diffusers except for the workstations located far away from the air supply or right under the exhaust grills (Haghighat et al 1996). Underfloor ventilation with a swirl air diffuser on the floor has the potential to reduce the exposure of a manikin inside an office cubical to the pollutant emitted outside the cubical by a factor of 2-3 (Kong, Zhang, and Wang 2014).…”
Section: Ventilationmentioning
confidence: 99%
“…Semi-open partitions between occupants can be used to form a personal cubical around each occupant to change the air distribution pattern and reduce the cross contamination (Shaw et al 1993a&b, Zhang et al 1994, Haghighat et al 1996, Kong, Zhang, and Wang 2014, and Kong 2019. Concentrations in a non-source containing cubical can be reduced by a factor of 1.1 to 3.6 in mixing type ventilation system with square or linear ceiling air diffusers except for the workstations located far away from the air supply or right under the exhaust grills (Haghighat et al 1996). Underfloor ventilation with a swirl air diffuser on the floor has the potential to reduce the exposure of a manikin inside an office cubical to the pollutant emitted outside the cubical by a factor of 2-3 (Kong, Zhang, and Wang 2014).…”
Section: Ventilationmentioning
confidence: 99%
“…In this sense, proper distribution of airflow and use of physical barriers can decrease the spreading of aerosol particles, thus further reducing the risk of human infection (Xu et al 2020). The critical factors impacting indoor airflow distribution include ventilation mode (location and design of air diffusers) as well as supply airflow rate (Bjorn and Nielsen 2002) (Lv et al 2019) (Haghighat et al 1996). In case of physical barrier and air deflectors, the focus will be on large and open space (Lv et al 2019) (Dominguez Espinosa and Glicksman 2017).…”
Section: Introductionmentioning
confidence: 99%
“…31 Another study showed that the contaminant removal effectiveness (CRE) was similar for the floor pollutant source and the desktop pollutant source under MV. 32 However, with the occurrence of the airflow short-circuiting, the CRE with the floor pollutant source was higher than with the desktop pollutant source under MV. 33 For displacement ventilation (DV), a peak of contaminant concentration at the breathing level was found when the contaminant was exhaled by the source manikin.…”
Section: Introductionmentioning
confidence: 96%